2019
DOI: 10.1111/tpj.14442
|View full text |Cite|
|
Sign up to set email alerts
|

Interactions between Transport Protein Particle (TRAPP) complexes and Rab GTPases in Arabidopsis

Abstract: Transport Protein Particle II (TRAPPII) is essential for exocytosis, endocytosis, protein sorting and cytokinesis. In spite of a considerable understanding of its biological role, little information is known about Arabidopsis TRAPPII complex topology and molecular function. In this study, independent proteomic approaches initiated with TRAPP components or Rab-A GTPase variants converge on the TRAPPII complex. We show that the Arabidopsis genome encodes the full complement of 13 TRAPPC subunits, including four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
73
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(79 citation statements)
references
References 89 publications
(190 reference statements)
6
73
0
Order By: Relevance
“…Previous studies with Arabidopsis have shown that Rab-GTP polypeptides are found on almost all intracellular membranes and appear to be involved in a coordinated network for intracellular trafficking of important substances. Some are also regulated by the Transport Protein Particle II (TRAPPII) system, which facilitates exchange between GTP and GDP and thereby can activate or repress Rab-GTP [10,59]. The models generated for this network are based on evidence from Arabidopsis tissues grown under non-stressed conditions [10,40,60].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies with Arabidopsis have shown that Rab-GTP polypeptides are found on almost all intracellular membranes and appear to be involved in a coordinated network for intracellular trafficking of important substances. Some are also regulated by the Transport Protein Particle II (TRAPPII) system, which facilitates exchange between GTP and GDP and thereby can activate or repress Rab-GTP [10,59]. The models generated for this network are based on evidence from Arabidopsis tissues grown under non-stressed conditions [10,40,60].…”
Section: Discussionmentioning
confidence: 99%
“…Some are also regulated by the Transport Protein Particle II (TRAPPII) system, which facilitates exchange between GTP and GDP and thereby can activate or repress Rab-GTP [10,59]. The models generated for this network are based on evidence from Arabidopsis tissues grown under non-stressed conditions [10,40,60]. In the latest model [10], RabD protein is associated with the Rough Endoplasmic Reticulum (RER), while RabB and RabA are localized in the Golgi and trans-Golgi network/Early endosome (TGN/EE), respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TRAPPII have also been pointed as a guanine exchange factors (GEFs) for RabA GTPases [88,89]. RabA GTPases can regulate membrane fusion events and other cell organelle processes once they are recruited to their speci c membrane compartment and activated by their cognate RabGEF.…”
Section: Vesicle Mediated Tra Cking and Protein Transportmentioning
confidence: 99%